PENGARUH JARAK TURBIN ANGIN SAVONIUS TIPE-U SUMBU VERTIKAL DENGAN SUMBER BUANGAN ANGIN EXHAUST FAN KITCHEN TERHADAP UNJUK KERJA PROTOTIPE PEMBANGKIT LISTRIK TENAGA BAYU - Dharma Pawitra, Ida Bagus Gede; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM, 2023)
Energy needs in Indonesia are increasing, especially in the realization of electricity consumption which reached 20.18 TWh in July 2020. Using exhaust wind energy from exhaust fans as an alternative source of wind energy is considered quite effective because the characteristics of the wind produced are stable. The method used in This research is quantitative and the purpose of this research is to get the optimal distance from the vertical axis of the savonius wind turbine to the exhaust fan. Setting the distance of the turbine is done by adjusting the position of the wind turbine to the exhaust fan with 4 test distances, namely 10 cm, 20 cm, 30 cm and 50 cm. The results of this study are a distance of 10 cm with a 40 ohm load, the output power is 1.74 watts with an efficiency of 23%, an 80 ohm load, the output power is 1.4 watts with an efficiency of 18%, a 120 ohm load, the output power is 1.215 watts with an efficiency of 16%. , a 160 ohm load produces 0.91 watts of output power with an efficiency of 12%, a 200 ohm load produces 0.91 watts of output power with an efficiency of 12%. distance of 50 cm 40 ohm load output power generated 0.4 watts with 11% efficiency, 80 ohm load output power generated 0.19 watts with 5% efficiency, 120 ohm load output power generated 0 watts with 0% efficiency, 160 ohm load power the output is 0 watts with 0% efficiency, a 200 ohm load produces 0 watts output power with 0% efficiency, so the optimal distance for placing the turbine is 10 cm.